Medición del grado de integración del mercado de capitales del Perú con el mercado de capitales mundial a través del uso del CAPM: 2000-2010 - Cortez Cortez, Gaby (2010)
The general objective of the new global economy is the integration of economies and markets. The market for financial assets through the stock exchanges is no exception to this trend of market integration, so that investors can participate in either of the existing exchanges in the world. This paper uses the International CAPM Beta to measure the degree of integration of national stock market to the world market. This beta was obtained from a sample of major national companies that list their shares on the Lima Stock Exchange compared to the index of the world market such as the Standard & Poor’s 500, with the aim of showing correlations between these two markets. In the case of Peru we used this methodology to confirm that the application of this model will lead to expected results on the theory.